(untitled) (Journal of Innovation and Technology Polbeng Series on Informatics (INOVTEK Polbeng - Seri Informatika), 2025)
In the current digital era, stable and uninterrupted internet connectivity is the backbone of modern operations, demanding high availability and reliability. A key challenge is managing the inherent single point of failure associated with a single ISP connection. This study investigates the implementation and effectiveness of IP Service Level Agreement (IP SLA) and Policy-Based Routing (PBR) on a multi-homed network to achieve automated failover optimization. A virtual testbed was constructed using EVE-NG with a Cisco IOS C7200 image, and each test scenario was replicated five times to ensure data consistency. IP SLA was configured for proactive failure detection (parameters: timeout 5000 ms, threshold 500 ms, request-data-size 100, delay up 10, delay down 5), while PBR was used for VLAN-based traffic steering. The results indicate that this solution successfully steered traffic according to policy and achieved a consistent failover switchover time of 1.07–1.09 seconds (n=5), supported by Wireshark analysis, which documented up to 100% packet loss during the transition. The failure detection time, directly correlated with the IP SLA frequency, varied from 3.96 seconds (5-second frequency) to 45.63 seconds (60-second frequency). During the transition, router CPU load remained low at 3%, indicating high resource efficiency. This research concludes that the combination of IP SLA and PBR is an effective solution for enhancing the resilience and service continuity of multi-homed networks with minimal computational overhead.